Mediaeval Studies in Honor of Jeremiah Dennis Matthias Ford. Edited by Urban T. Holmes, Jr. and Alex J. Denomy, C. S. B. Harvard University Press, 1948, xxxii + 376 págs. y 10 ilustraciones. Ramón Menéndez Pidal, Un viejo romance cantado por Sabbatai Ceví. Págs. 185-190. Francis M. Rogers, Insular Portuguese Pronunciation: Alleged Flemish Influence. Págs. 211-221. - Lida de Malkiel, Maria Rosa (El Colegio de México, 2007)
Se reseñaron: Mediaeval Studies in Honor of Jeremiah Dennis Matthias Ford. Editedby Urban T. Holmes, Jr. and Alex J. Denomy, C. S. B. HarvardUniversity Press, 1948, xxxii + 376 págs. y 10 ilustraciones.Ramón Menéndez Pidal, Un viejo romance cantado por Sabbatai Ceví.Págs. 185-190.Francis M. Rogers, Insular Portuguese Pronunciation: Alleged FlemishInfluence. Págs. 211-221.